“Scanning the Landscape for Some Guidance in That Emptiness”: The (De)Construction of Meaning in Blood Meridian - Santos, Márcio da Silva (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
In the diegesis of Cormac McCarthy’s Blood Meridian (1985), the decline of religious fervor is accompanied by a trenchant crisis of signification. The need for the reassertion of meaning leads to the advent of an alternative worldview that offers a mythologized view of war as a suitable substitute for religion, but neither of these competing worldviews (nor any other) gets a firm foothold. What is particularly striking, however, is that this conflict surpasses the diegesis, since the narrator – just like the characters – is also torn between these two worldviews, craving for a stable and verifiable way of reading reality, for a paradigm that can be validated beyond any doubt. He fails, in the process creating a schizophrenic narration and, consequently, negating the possibility of verifying meaning.